Nematode parasites of four species of Carangoides (Osteichthyes: Carangidae) in New Caledonian waters, with a description of Philometra dispar n. sp. (Philometridae) - Moravec, František (Parasite, 2016)
Parasitological examination of marine perciform fishes belonging to four species of Carangoides, i.e. C. chrysophrys, C. dinema, C. fulvoguttatus and C. hedlandensis (Carangidae), from off New Caledonia revealed the presence of nematodes. The identification of carangids was confirmed by barcoding of the COI gene. The eight nematode species found were: Capillariidae gen. sp. (females), Cucullanus bulbosus (Lane, 1916) (male and females), Hysterothylacium sp. third-stage larvae, Raphidascaris (Ichthyascaris) sp. (female and larvae), Terranova sp. third-stage larvae, Philometra dispar n. sp. (male), Camallanus carangis Olsen, 1954 (females) and Johnstonmawsonia sp. (female). The new species P. dispar from the abdominal cavity of C. dinema is mainly characterised by the body length (5.14 mm), the lengths of markedly unequal spicules (163 and 96 μm) and gubernaculum (102 μm long) provided with a dorsal protuberance and a small, reflexed dorsal barb on its posterior portion. The finding of C. bulbosus represents the first record of this parasite a century after its discovery; the first study of this species by scanning electron microscopy (SEM) enabled detailed redescription. The finding of Johnstonmawsonia sp. in C. fulvoguttatus is the first record of a rhabdochonid nematode from a host belonging to the Carangidae family. Johnstonmawsonia africana Moravec & Puylaert, 1970 and J. campanae Puylaert, 1973 are transferred to Prosungulonema Roytman, 1963 as P. africanum (Moravec & Puylaert, 1970) comb. n. and P. campanae (Puylaert, 1973) n. comb.